Cutting edge advertising : how to create the world's best print for brands in the 21st century - Aitchison, Jim (Pearson/Prentice Hall, 2008)
Now revised and updated, this classic book is still the definitive step-by-step guide to creating cutting edge print ads. It covers everything from how advertising works, how brand-building methodologies are changing, how to get an idea, and how copy and art should be crafted. It demystifies the advertising creative process, with page after page of practical, inspiring and often controversial advice from such masters as David Abbott, Bob Barrie, Tim Delaney, David Droga, Neil French, Marcello Serpa, and dozens more. Over 200 print ads and case histories reveal the creative processes at work in world-famous agencies in the US, UK, Asia and Australia. This new edition also includes an exclusive section featuring winning ads from the World Press Awards. No other book takes you on such a journey through the minds of advertising¿s creative leaders.